High-speed and efficient silicon modulator based on forward-biased pin diodes - Akiyama, Suguru; Usuki, Tatsuya (Frontiers in Physics, 2014)
Silicon modulators, which use the free-carrier-plasma effect, were studied, both analytically and experimentally. It was demonstrated that the loss-efficiency product, α · VπL, was a suitable figure of merit for silicon modulators that enabled their intrinsic properties to be compared. Subsequently, the dependence of VπL on frequency was expressed by using the electrical parameters of a phase shifter when the modulator was operated by assuming a simple driving configuration. A diode-based modulator operated in forward biased mode was expected from analyses to provide more efficient operation than that in reversed mode at high frequencies due to its large capacitance. We obtained an α · VπL of 9.5 dB·V at 12.5 GHz in experiments by using the fabricated phase shifter with pin diodes operated in forward biased mode. This α · VπL was comparable to the best modulators operated in depletion mode. The modulator exhibited a clear eye opening at 56 Gb/s operated by 2 V peak-to-peak signals that was achieved by incorporating such a phase shifter into a ring resonator.